Prevention of foot ulcers in the at‐risk patient with diabetes: a systematic review. (19th January 2020) - van Netten, Jaap J.; Raspovic, Anita; Lavery, Lawrence A.; Monteiro‐Soares, Matilde; Rasmussen, Anne; Sacco, Isabel C. N.; Bus, Sicco A.
Abstract: Prevention of foot ulcers in patients with diabetes is important to help reduce the substantial burden on both patient and health resources. A comprehensive analysis of reported interventions is needed to better inform healthcare professionals about effective prevention. The aim of this systematic review is to investigate the effectiveness of interventions to help prevent both first and recurrent foot ulcers in persons with diabetes who are at risk for this complication. We searched the available medical scientific literature in PubMed, EMBASE, CINAHL, and the Cochrane databases for original research studies on preventative interventions. We screened trial registries for additional studies not found in our search and unpublished trials. Two independent reviewers assessed data from controlled studies for methodological quality, and extracted and presented this in evidence and risk of bias tables. From the 13, 490 records screened, 35 controlled studies and 46 non‐controlled studies were included. Few controlled studies, which were of generally low to moderate quality, were identified on the prevention of a first foot ulcer. For the prevention of recurrent plantar foot ulcers, there is benefit for the use of daily foot skin temperature measurements, and for therapeutic footwear with demonstrated plantar pressure relief, provided it is consistently worn by the patient. For prevention of ulcer recurrence, there is some evidence for providing integrated foot care, and no evidence for a single session of education.Surgical interventions have been shown effective in selected patients, but the evidence base is small. Foot‐related exercises do not appear to prevent a first foot ulcer. A small increase in the level of weight‐bearing daily activities does not seem to increase the risk for foot ulceration. The evidence base to support the use of specific self‐management and footwear interventions for the prevention of recurrent plantar foot ulcers is quite strong. The evidence is weak for the use of other, sometimes widely applied, interventions, and is practically non‐existent for the prevention of a first foot ulcer and non‐plantar foot ulcer.